2000
DOI: 10.1034/j.1600-0714.2000.290103.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile ossifying fibroma. An analysis of eight cases and a comparison with other fibro‐osseous lesions

Abstract: Juvenile ossifying fibroma (JOF) is a well-defined clinical and histological entity that has recently been separated from other fibro-osseous lesions, including cemento-ossifying fibromas. Its biological behaviour is well defined, but unexplained. Its behaviour, clinical and histological appearance, however, bears resemblance to osteofibrous dysplasia of long bones, a lesion that in some cases has been reported to be part of a spectrum of diseases associated with adamantinoma, thus accounting for its variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 4 publications
4
65
0
3
Order By: Relevance
“…A fibrocellular stroma containing trabeculae of osteoid and woven bone was present in all cases discussed above. Osteoblastic rimming was present in all cases of JOF reported by William et al, 9 in some cases of JOF studied by Slootweg et al 14 and in the present case.…”
Section: Discussionsupporting
confidence: 54%
“…A fibrocellular stroma containing trabeculae of osteoid and woven bone was present in all cases discussed above. Osteoblastic rimming was present in all cases of JOF reported by William et al, 9 in some cases of JOF studied by Slootweg et al 14 and in the present case.…”
Section: Discussionsupporting
confidence: 54%
“…PM usually show immunoreactivity for EMA and vimentin [2,4]. Granados et al reported EMA immunoreactivity in OF [11]; in addition it was shown that OF also express SMA and CD10 with lack of expression of CD34, S100 and cytokeratins [11,21]. Most of meningiomas are immunoreactive for antibodies directed against S-100 protein; similarly, CD10 is expressed in a high percentage of PM; therefore, immunohistochemical stains may not be able to distinguish all cases and may lead to an erroneous diagnosis of PM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an unusual clinical presentation with apparent aggressive and destructive growth may be expected when the lesion is encountered in a younger patient. 18,19 In our patient, the lesion was initiated at a younger age but was neglected by the patient and/or was not detected at that time.…”
Section: Discussionmentioning
confidence: 99%